Heteroatom‐Doped Porous Carbon Nanosheets: General Preparation and Enhanced Capacitive Properties. Issue 46 (5th October 2016) - Hao, Xiaodong; Wang, Jie; Ding, Bing; Shen, Laifa; Xu, Yunling; Wang, Ya; Chang, Zhi; Dou, Hui; Lu, Xiangjun; Zhang, Xiaogang
Abstract: High‐performance electrical double‐layer capacitors (EDLCs) require carbon electrode materials with high specific surface area, short ion‐diffusion pathways, and outstanding electrical conductivity. Herein, a general approach combing the molten‐salt method and chemical activation to prepare N‐doped carbon nanosheets with high surface area (654 m 2  g −1 ) and adjustable porous structure is presented. Owing to their structural features, the N‐doped carbon nanosheets exhibited superior capacitive performance, demonstrated by a maximum capacitance of 243 F g −1 (area‐normalized capacitance up to 37 μF cm −2 ) at a current density of 0.5 A g −1 in aqueous electrolyte, high rate capability (179 F g −1 at 20 A g −1 ), and excellent cycle stability. This method provides a new route to prepare porous and heteroatom‐doped carbon nanosheets for high‐performance EDLCs, which could also be extended to other polymer precursors and even waste biomass. Abstract : Molten‐salt activation : A general approach combining the molten‐salt method and chemical activation to prepare heteroatom‐doped carbon nanosheets was developed. Owing to their large surface area and adjustable porous structure, the N‐doped carbon nanosheets exhibit significantly enhanced capacitive properties in electrical double‐layer capacitors (see figure).